Manajemen Sarana Prasarana untuk Meningkatkan Pembelajaran Al-Qur’an di Pondok Pesantren Ma’had Alfatah - Rasminto, Rasminto; M. Nasor; Nur Widiastuti (UNISAN JURNAL, 2025)
This study aims to analyze the implementation of educational facilities and infrastructure management in improving the quality of Qur’anic learning at Ma’had Alfatah Islamic Boarding School. This research employs a descriptive qualitative approach using observation, in-depth interviews, and documentation techniques. The findings indicate that facilities management is carried out through systematic stages, including needs assessment, procurement of learning facilities, regular maintenance, and evaluation of facility effectiveness. The management process involves providing tahfiz rooms, standardized Qur’an learning texts, audio devices, adequate lighting, and a supportive learning environment. The pesantren leadership plays a crucial role in coordination, supervision, and quality control of learning activities. Effective management of facilities has contributed significantly to improving students’ Qur’anic reading skills, fluency, and comprehension. Challenges include budget limitations, the need for additional facilities, and inadequate maintenance of certain equipment. Overall, the study concludes that structured and continuous facilities management is essential for enhancing the quality of Qur’anic education in Islamic boarding schools.